Treatment of Systemic Lupus Erythematosus with Anti SSA and SSB Positive Pregnancies - Robby Satria Putra; Najirman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Systemic lupus erythematosus (SLE) is autoimmune disease that results in inflammation in various organ systems, frequent recurrences in the clinical course characterized by the production of antibodies against core antigens. Pregnancy will trigger flares. Increased intravascular volume in pregnancy can worsen abnormal heart and kidney function. Increasing the glomerular filtration rate by 50% exacerbated previously stable proteinuria. Pregnancy-induced hypercoagulability increases the risk of thrombosis. Anti-Ro/SSA was found in 35% of SLE patients and anti-La / SSB was found in 15% of SLE patients. The presence of Ro and La antibodies puts the fetus at a risk of developing neonatal lupus erythematosus (NLE) 6-13% and can reach up to 25% if the mother has previously given birth to a child with NLE. Neonatal lupus erythematosus including congenital heart block or cutaneous lupus. Congenital heart block (CHB) is a very serious complication. The American College of Rheumatology (ACR) recommends serial fetal echocardiography from 16 weeks of gestation continuing through to 26 weeks. Pregnancies with grade I and II CHB are treated with oral dexamethasone 4 mg daily because fluorinated glucocorticoids such as dexamethasone and betamethasone can cross the placenta, however, this therapy cannot be given in third-degree heart block. Early diagnosis and therapy will reduce the risk of congenital heart block in neonates after birth.